Draft Genome Sequence of Alcanivorax sp. Strain KX64203 Isolated from Deep-Sea Sediments of Iheya North, Okinawa Trough - Zhang, Huan (Genome Announc, 2016)
This report describes the draft genome sequence of Alcanivorax sp. strain KX64203, isolated from deep-sea sediment samples. The reads generated by an Ion Torrent PGM were assembled into contigs, with a total size of 4.76 Mb. The data will improve our understanding of the strain’s function in alkane degradation.